PENGEMBANGAN SISTEM PELAYANAN SURAT IJIN BERLAYAR DI PELABUHAN PERIKANAN PANTAI KLIDANG LOR - Darmawan, Wachid; Nisa, Rohmatun; Kurniawan, Muhammad Faizal (Bapelitbang Kabupaten Batang, 2025)
Services for issuing ship sailing permits include departure and arrival permits at the Klidang Lor Beach Fisheries Port, Batang Regency faces inefficiencies due to a manual process based on Microsoft Excel and Word. The main problems include slow data recapitulation, difficulty in archival retrieval, and long waiting times for ship owners. This research aims to develop an integrated information system to overcome these issues. The system was designed using the waterfall method, which includes five stages, from analysis to treatment. The system's functionality and feasibility were tested comprehensively through white-box testing methods. The result of this research is a system that enables ship owners to submit departure and arrival data digitally. This system successfully automates data processing by officers and provides a feature for the instant printing of daily and monthly reports for ship owners and the head of the port. The system has successfully improved the efficiency and effectiveness of the administrative process at the Klidang Lor Coastal Fishing Port, thus providing significant benefits for all parties involved.